Spectral modeling of Cassini-VIMS data to investigate the surface properties of Enceladus - Fryer, Owain (author) (2021)
Much research has been completed on Saturn's icy moon Enceladus when Cassini detected plumes in the south pole region. Studies show the south pole region has ice particles with larger grain sizes and a higher percentage of crystallinity than the rest of the moon due to these plumes. However, this trend also appears at around 30 degrees North, 90 degrees West in the northern hemisphere that is unexplainable. This thesis uses infrared spectral data from the Cassini mission and a reflectance model to identify the parameters of the surface ice from different regions on the surface to explain why the features in the northern hemisphere match that of the plume region. This study finds the grain size, porosity, roughness, formation temperature, and crystallinity of the surface ice to compare each zone. The parameters found in this study suggest that the region underwent recent resurfacing caused by activity from within the moon. Aerospace Engineering